Long-term variability of drought indices in the Czech Lands and effects of external forcings and large-scale climate variability modes - Mikšovský, Jiří; Brázdil, Rudolf; Trnka, Miroslav; Pišoft, Petr (Climate of the Past, 2019)
While a considerable number of records document the temporal variability of droughts for central Europe, the understanding of its underlying causes remains limited. In this contribution, time series of three drought indices (Standardized Precipitation Index – SPI; Standardized Precipitation Evapotranspiration Index – SPEI; Palmer Drought Severity Index – PDSI) are analyzed with regard to mid- to long-term drought variability in the Czech Lands and its potential links to external forcings and internal climate variability modes over the 1501–2006 period. Employing instrumental and proxy-based data characterizing the external climate forcings (solar and volcanic activity, greenhouse gases) in parallel with series representing the activity of selected climate variability modes (El Niño–Southern Oscillation – ENSO; Atlantic Multidecadal Oscillation – AMO; Pacific Decadal Oscillation – PDO; North Atlantic Oscillation – NAO), regression and wavelet analyses were deployed to identify and quantify the temporal variability patterns of drought indices and similarity between individual signals. Aside from a strong connection to the NAO, temperatures in the AMO and (particularly) PDO regions were disclosed as one of the possible drivers of inter-decadal variability in the Czech drought regime. Colder and wetter episodes were found to coincide with increased volcanic activity, especially in summer, while no clear signature of solar activity was found. In addition to identification of the links themselves, their temporal stability and structure of their shared periodicities were investigated. The oscillations at periods of approximately 60–100 years were found to be potentially relevant in establishing the teleconnections affecting the long-term variability of central European droughts.